2019
DOI: 10.11114/jets.v7i12.4491
|View full text |Cite
|
Sign up to set email alerts
|

A Review into Effective Classroom Management and Strategies for Student Engagement: Teacher and Student Roles in Today’s Classrooms

Abstract: A teacher’s role encompasses far more than just imparting curricula outcomes to their students: they need to equip students with the necessary tools to experience social and academic success both inside the classroom and beyond it. Teachers need to empower students with the means to critically analyse the world around them in order to develop into critical independent thinkers. Students need to be proficient in utilising skills associated with higher levels of thinking, that will empower them with the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…Moving on to the second part of the research, the participants focused on five elements to make changes in their teaching. The quality of instruction, appropriateness level of instructions, incentive and time as suggested by Slavin [17,18] were highlighted as the needed elements to help them to achieve effective teaching, but the teachers claimed that teachers need to focus on their teaching performance and students' performance [10], teachers' motivation [31] and classroom management [19,25,29,35] to guide them to be more reflective, creative and to think critically to find relevancy in planning and choosing the materials [33,45] as well as effective approaches [30,34] to deliver their instructions successfully [10,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving on to the second part of the research, the participants focused on five elements to make changes in their teaching. The quality of instruction, appropriateness level of instructions, incentive and time as suggested by Slavin [17,18] were highlighted as the needed elements to help them to achieve effective teaching, but the teachers claimed that teachers need to focus on their teaching performance and students' performance [10], teachers' motivation [31] and classroom management [19,25,29,35] to guide them to be more reflective, creative and to think critically to find relevancy in planning and choosing the materials [33,45] as well as effective approaches [30,34] to deliver their instructions successfully [10,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Slavin [17,18] as well as Darling-Hammond [1] found that reflected on accurate elements upsurged teachers' teaching quality for students' achievement. Thus, they suggested teachers to use reflective practive to be more flexible and creative enough [3,4] to plan the teaching, to manage the classroom and to deliver the lesson by taking into their consideration of students' prior skills, information, motivation and time needed to learn the lesson [11,24,30]. In addition, teachers need to bear in mind; the students' learning process was affected by teachers' teaching styles and students' individual's behaviour, cognitive needs, thoughts and feelings [16,31,32] to enable the students to be active learners [3,4] to learn, explore, discover and create a better understanding of the subject they learn [1,19,[33][34][35] based on their learning pace [26,35].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have documented the successful teaming up of teachers, inclusive service providers, and parents in implementing support plans for students with disabilities and those who are academically at-risk (Sifiso and Matome, 2018). Consistently, supported implementation of inclusive education policy resulted in increase in academic skills, engagement in class activities, interactions with peers, and student-initiated interactions for all learners (Hayley and Ingrid, 2019). Despite the enactment and domestication of international laws on inclusive education, there is still a big gap between policy frameworks and inclusive practices on the ground, (UNICEF, 2019).…”
Section: Structural Readjustment In Schoolsmentioning
confidence: 99%
“…They occur in various forms, including encouragement, gifting, appreciation, and providing attention. According to Franklin and Harrington (2019), teachers are aware of the fact that appreciating leaners for their positive behaviors makes them avoid searching for, and consider being involved in disruptive behavior. In other words, overlooking students increase their chances of disrupting lessons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, there are likely to disturb their fellow learners to acquire their focus, not obeying the need to talk in turns, failing to complete class assignments, and generally 'being off tasks.' These inappropriate actions influence the performance of both teachers and students as they stimulate stress (Franklin & Harrington, 2019). Moreover, such behaviors limit the time allocated to cover all the necessary curriculum benchmarks; because teachers spend considerable amounts of time addressing classroom disruptions, thus making it challenging to attain a desirable atmosphere.…”
Section: Introductionmentioning
confidence: 99%